2018
DOI: 10.4103/aca.aca_19_18
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled levosimendan versus intravenous levosimendan in patients with pulmonary hypertension undergoing mitral valve replacement

Abstract: Context:Inhaled levosimendan may act as selective pulmonary vasodilator and avoid systemic side effects of intravenous levosimendan, which include decrease in systemic vascular resistance (SVR) and systemic hypotension, but with same beneficial effect on pulmonary artery pressure (PAP) and right ventricular (RV) function.Aim:The aim of this study was to compare the effect of inhaled levosimendan with intravenous levosimendan in patients with pulmonary hypertension undergoing mitral valve replacement.Settings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…have used bilateral ESB to provide postoperative analgesia after cardiac surgery through midsternotomy. They observed significantly improved pain scores at rest and during coughing in patients who received ESB for up to 48 h.[ 12 ]…”
Section: Erector Spinae Blockmentioning
confidence: 99%
“…have used bilateral ESB to provide postoperative analgesia after cardiac surgery through midsternotomy. They observed significantly improved pain scores at rest and during coughing in patients who received ESB for up to 48 h.[ 12 ]…”
Section: Erector Spinae Blockmentioning
confidence: 99%
“…They found that pulmonary artery pressure was significantly reduced in both milrinone and levosimendan groups compared to the placebo. Moreover, levosimendan exerted prolonged pulmonary vasodilatory effects (3 hours vs. milrinone's 30 minutes), and both agents selectively dilated pulmonary vasculature without adverse effects [33].…”
Section: Inhaled Levosimendanmentioning
confidence: 99%
“…Given the vasodilatory properties of LS, it could distend pulmonary vasculature and vasculature of the venous system, causing a reduction in both RV preload and afterload, while, given the inotropic action of the drug, it could enhance RV contractility [ 32 , 33 ]. Although LS is a potentially favorable agent in treating PH and associated RVF, few data exist regarding its use in patients with PH undergoing cardiac surgery and the impact of extracorporeal circulation on its pharmacokinetic and pharmacodynamic properties.…”
Section: Introductionmentioning
confidence: 99%